Influence of plant–pollinator interactions on the assembly of plant and hummingbird communities. (10th November 2016) - Wolowski, Marina; Carvalheiro, Luísa G.; Freitas, Leandro
Summary: Understanding how ecological processes structure species assemblages is a central issue in community ecology. While the influence of plant–pollinator interactions on each other's evolution is well recognized, their role in the assembly of interdependent communities of plants and pollinators is still unclear. Using data from seven communities of hummingbirds and plants that they pollinate from two tropical rain forest types (lowland and montane), we evaluated phylogenetic relationships and signal of functional traits, over space and time, to test predictions on the main processes (environmental filtering, facilitation or competition) that are driving these hummingbird–plant assemblages. Our findings suggest that the main processes driving these assemblages varied between hummingbirds and plants and between habitats, and even among communities at the same habitat. The non‐conserved floral trait and the phylogenetic patterns (even or random) give support to the hypothesis of facilitation or competition as processes regulating the composition of plant assemblages. Moreover, the positive relationship between fitness and flowering synchrony suggests facilitation as the most important mechanism for montane plant communities. Distinctively, for lowland plant communities, the combination of non‐conserved traits and clustered phylogenetic patterns may be a result of either adaptive radiation or biotic filtering driven by a particular pollinator species that plays a main role as plant community organizer. Lastly, evidence of trait conservatism, together with clustered or even phylogenetic patterns, suggests that facilitation or competition may drive the assembly of montane hummingbird communities, despite the predominance of random phylogenetic patterns. Synthesis . Overall, we present a pathway to identify central ecological processes that may drive the assembly of plant–pollinator communities. We show that different processes related with pollination that vary in space and time may contribute to the assembly of the interdependent tropical communities of plants and pollinators. These findings highlight the importance of considering ecological interactions when evaluating community assembly processes. Abstract : Overall, we present a pathway to identify central ecological processes that may drive the assembly of plant–pollinator communities. We show that different processes related with pollination that vary in space and time may contribute to the assembly of the interdependent tropical communities of plants and pollinators. These findings highlight the importance of considering ecological interactions when evaluating community assembly processes.